NMR observation of individual molecules of hydration water bound to DNA duplexes: direct evidence for a spine of hydration water present in aqueous solution. - Liepinsh, E (1992)
The residence times of individual hydration water molecules in the major and minor grooves of DNA were measured by nuclear magnetic resonance (NMR) spectroscopy in aqueous solutions of d-(CGCGAATTCGCG)2 and d-(AAAAATTTTT)2. The experimental observations were nuclear Overhauser effects (NOE) between water protons and the protons of the DNA. The positive sign of NOEs with the thymine methyl groups shows that the residence times of the hydration water molecules near these protons in the major groove of the DNA must be shorter than about 500 ps, which coincides with the behavior of surface hydration water in peptides and proteins. Negative NOEs were observed with the hydrogen atoms in position 2 of adenine in both duplexes studied. This indicates that a 'spine of hydration' in the minor groove, as observed by X-ray diffraction in DNA crystals, is present also in solution, with residence times significantly longer than 1 ns. Such residence times are reminiscent of 'interior' hydration water molecules in globular proteins, which are an integral part of the molecular architecture both in solution and in crystals.